Antimicrobial Compounds from Marine Invertebrates-Derived Microorganisms - Liu, Juan; H. Jung, Jee; Liu, Yonghong (Current Medicinal Chemistry, 2016)
It is known that marine invertebrates, including sponges, tunicates, cnidaria or mollusks, host affluent and various communities of symbiotic microorganisms. The microorganisms associated with the invertebrates metabolized various biologically active compounds, which could be an important resource for the discovery and development of potentially novel drugs. In this review, the new compounds with antimicrobial activity isolated from marine invertebrate-derived microorganisms in the last decade (2004-2014) will be presented, with focus on the relevant antimicrobial activities, origin of isolation, and information of strain species. New compounds without antimicrobial activity were not revealed.
Keywords: antimicrobial activity